PROTOTYPE APLIKASI GENERATE BARCODE BERBASIS WEB PADA PT. BIMASAKTI KARYAPRIMA - Ilamsyah Ilamsyah; Agus Hidayatullah; Muhammad Aldino Dwi Putra (UNIVERSITAS RAHARJA, 2020)
PT. BimasaktiKaryaprima is a medium-sized company engaged in the shoe industry. In this company, there is a system to create barcode shoe data that still uses Libre Office, where in the implementation of the system there are several things that become obstacles, which includes the effectiveness and time efficiency in the process of inputting barcode shoes data, the form of manufacture which is still typing one by one the data that must be printed in making a barcode. With the above reasons, the author tries to provide an alternative problem solving by creating a barcode making system application where the user can input large amounts of data and can also process data import with CSV file extension, so that it will eliminate the way of making barcode data with the Libre Office which has been running at PT. Bimasaktikaryaprima. At this writing the method used for collecting data through observation, interviews, literature studies and software design methods using the waterfall method.